2021
DOI: 10.7759/cureus.14459
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Road Traffic Accident Fatalities in Karachi, Pakistan: An Autopsy-Based Study

Abstract: BackgroundRoad traffic accident (RTA) fatalities account for a significant number of unnatural deaths in Pakistan. Hence, it is necessary to investigate RTA fatalities in order to implement measures to reduce them. In the present study, we aimed to assess the detailed epidemiological characteristics of RTA fatalities by analyzing the data obtained from medico-legal autopsies performed at the Jinnah Postgraduate Medical Centre (JPMC) in 2019 and 2020. We assessed age-and gender-based variations in the pattern o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 17 publications
5
7
1
Order By: Relevance
“…The results showed that there was a significant decrease in road traffic accidents during the lockdown period that may be caused by reduced traffic burden. 7 Our study did not reveal any statistically significant difference regarding age, gender, and area of belonging related to unnatural deaths in Sahiwal, but a quite evident difference was observed regarding the manner of death. The proportion of accidental deaths was increased from 4% to 36% which was contrary to a study conducted in Greece where such types of death cases were greatly reduced during a lockdown.…”
Section: Discussioncontrasting
confidence: 73%
“…The results showed that there was a significant decrease in road traffic accidents during the lockdown period that may be caused by reduced traffic burden. 7 Our study did not reveal any statistically significant difference regarding age, gender, and area of belonging related to unnatural deaths in Sahiwal, but a quite evident difference was observed regarding the manner of death. The proportion of accidental deaths was increased from 4% to 36% which was contrary to a study conducted in Greece where such types of death cases were greatly reduced during a lockdown.…”
Section: Discussioncontrasting
confidence: 73%
“…The decrease in number of admissions could also be attributed to a parents preferring to treat the child at home rather than taking the child to the hospital duet to fear of getting infected (26). A number of international studies have reported lockdown to decrease the numbers of road traffic accidents globally (29)(30)(31) which might be the reason for an overall decrease in the volume of admissions as reported by us and other studies (26)(27)(28). Lockdown is known to decrease the numbers of road traffic accidents resulting in non serious injuries but not those that result in serious injuries (32).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported this ratio in RTA as 6:1. 13 However, our results only included ocular injuries in RTA. In another study from India, males accounted for 77.6% and females 22.4%.…”
Section: Discussionmentioning
confidence: 99%